Religious Tolerance and Its Connection with Parenting Style: Examining from Four Dimensions - Indro Adinugroho; Rizki Saliha Paramaiswari (Universitas Ahmad Dahlan, 2022)
Religious tolerance is a fundamental part of Indonesia, a country with diversity in religions and beliefs. As an attempt to serve social, political, and cultural stability among groups in Indonesia, Indonesians agreed to live together in harmony through the Pancasila, where all religions and beliefs must be honored. Therefore, specific beliefs and attitudes in how we live in Indonesia must be addressed since early childhood through education in school, public, and family. Parenting style becomes one of the significant issues affecting children's life span development so that they can be excellent as the future generation. This argument is constructed based on the previous studies that parenting style affects the perception and behavior of children. Therefore, this study examines the connection between parenting style and religious tolerance as the dependent variable. The result shows that based on four dimensions of parenting style, participants with the authoritative style show a higher score on the religious tolerance scale. In contrast, participants with neglecting style tend to have the lowest score in religious tolerance. This result reveals that parenting might be considered in child development and fulfilling child rights.